Combined effects of exploitation and environmental change on life history: a comparative analysis on Atlantic herring. (29th November 2022) - Beaudry-Sylvestre, Manuelle; Benoît, Hugues P; Hutchings, Jeffrey A
Abstract: The consequences of fisheries-induced evolution on stock productivity and yield depend, to a large extent, on the general prospects for growth and survival. Here, we compare the selection pressures imposed by two distinct patterns of exploitation—principally targeting spawning or non-spawning aggregations—on age at maturity among 15 Canadian stocks of Atlantic herring ( Clupea harengus ) that have exhibited a consistent pattern of length-at-age responses to common large-scale environmental drivers since the 1960s. In accordance with expectations for maturity-dependent harvesting, the establishment of a spawner-targeted fishery in the southern Gulf of St. Lawrence coincided with a shift towards delayed maturity in both resident stocks, whereas stocks elsewhere subject to fisheries that also exploited juveniles more commonly exhibited trends towards earlier maturity. Despite these differences, we find that environmentally driven changes in length at maturation, combined with total mortality, may overwhelmingly determine lifetime reproductive success and possibly fitness. By linking phenotypic changes experienced in the juvenile period to simple correlates of egg production in mature age classes, our study highlights the importance of managing fisheries in the context of ubiquitous but contrasting environmental constraints on life histories.